PKM limbah kardus air mineral dan kertas koran menjadi handycrafts berbasis produk rumahan - Aswar Aswar; Agussalim Djirong; Asmita Asmita (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The purpose of this Community Partnership Program activity is how to synergize housewives in the Kalimata Gowa housing complex with environmental conditions, both inside and outside the complex related to the use of used packaging boxes and newspapers which are types of inorganic waste which usually becomes one of the causes of environmental pollution, which although not very significant with direct pollution of environmental impacts. Environmental pollution caused by inorganic waste such as used cardboard boxes, as well as unused newspapers is fairly young waste decomposed compared to other plastic packaging wastes. However, if this is not taken seriously, over time paper-type waste which is usually mostly from the activities of residents, industries, shops, tourism, hotels can be a source of pollution that is quite disturbing to the surrounding environment. The method used in this training is direct practice towards the target (housewives) based on consideration of solutions and output targets that are expected through a production approach and practical work management. As for what is produced from this training is the training target (housewives) can make home-based handicraft products in the form of storage with cardboard material and newspaper, as well as the formation of creative housewives groups complex in the Kalimata Gowa housing complex.